Quality of E-KTP Service at the Gowa Regency Population and Civil Registration Office - Nursyam, Muh.; Nur, Andi Cudai; H, Herman (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
This research aims to find out the readiness of the government, in this case the Majene Regency Diskominfo to realize This study aims to determine the quality of e-KTP services at the Office of Population and Civil Registration (DUKCAPIL) in Gowa Regency. This research is qualitative with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The data analysis techniques used consisted of data condensation, data presentation, and conclusion drawing. The research results indicate that: (1) the quality of e-KTP services at the Office of Population and Civil Registration (DUKCAPIL) in Gowa Regency can be identified through five indicators described as follows: (a) Transparency is not optimal due to discrepancies between the contents of the SOP and posters displayed at the DUKCAPIL office related to the free cost of making e- KTPs; (b) Accountability is quite optimal as all services for the community, as well as requests and complaints from the public, can be conveyed well without obstacles; (c) Conditionality is not optimal due to inadequate facilities and infrastructure, such as limited waiting room space; (d) Equal Rights are optimal as services are provided without discrimination, ensuring equal opportunity for all, both in manual services and via the website; (e) Balance of Rights and Obligations is optimal as employees are capable of explaining and responding to all service users' questions and complaints. (2) Supporting and inhibiting factors of the quality of e-KTP services at the Office of Population and Civil Registration (DUKCAPIL) in Gowa Regency are as follows: (a) Employees always coordinate with each other and remind one another to oversee performance and responsibilities in service delivery; (b) Service inhibitors include inadequate facilities and infrastructure and limited waiting room space, causing congestion and frustration among the public while waiting in line.